Performance study of adaptive modulation and coding schemes in WiMAX OFDM-based system - Al-Qahtani, A.H.; Aldhaheri, R.W. (2009 IEEE 9th Malaysia International Conference on Communications, 2009)
In this paper, we study the performance of an Orthogonal Frequency Division Multiplexing (OFDM) WiMAX transmission system with adaptive modulation and coding (AMC) over different fading channels. An explanation necessary to understand the block diagram of the system is briefly given and a MATLAB code is written to simulate the basic processing involved in this system. The simulation is performed for Fixed and Mobile WiMAX and the performance measures we presented in this paper are: the bit error rate (BER), and the spectral efficiency versus the ratio of bit energy to noise power spectral density (Eb/No). The system parameters used in this paper are based on IEEE 802.16 standards.